HISTOPATHOLOGICAL VIEW OF WHITE RATS HEART WITH FIBROSARCOMA POST VIROTHERAPY NEWCASTLE DISEASE VIRUS ISOLATE GIANYAR-1/AK/2014 - Simanihuruk, Brigietta Vincencia; Winaya, Ida Bagus Oka; Adi, Anak Agung Ayu Mirah (Buletin Veteriner Udayana, 2023)
Virotherapy is a type of cancer therapy that utilizes the properties of viruses to destroy cancer cells. This therapy uses an oncolytic virus can destroys cancer cells. In the study, the oncolytic virus used was the virusNewcastle Disease. Virus Newcastle Disease known to be non-pathogenic in mammals so that this virus can be used as a cancer treatment agent. This study aims to determine the histopathological description of Newcastle Disease virus virotherapy on the cardiac histology of white rats with fibrosarcoma. Mice were grouped into two treatment groups, namely P 0  (treatment 0) with fibrosarcoma treated with PBS and P 1 (treatment 1) with fibrosarcomas treated with a virus Newcastle Disease at a dose of 0,5 ml/2 8 HA units. Histopathological view of the heart of P 1 white rats shows hemorrhagic lesions, congestion, and edema. The results of the microscopic examination were then quantified by scoring and analyzed using non-parametric tests. The results of the observation showed that Newcastle Disease virotherapy did not give significant changes in hemorrhagic lesions, congestion and edema (P>0,05).